Comparative studies on production potential of natural and cultivated grasses and their nutrient utilization in mithun - PAL, D T; BUJARBARUAH, K M (The Indian Journal of Animal Sciences, 2014)
The availability of total green forages and its nutrients from natural grass pasture of mithun-inhabited area of Medziphema were estimated and its comparison was made with cultivated fodder (napier grass). Utilization of nutrients obtained from natural and napier grasses and their nutritive values were estimated through feeding trials on mithun calves. Total green forage biomass production and nurtients availability was more from cultivated napier than natural grass. Availability of DM was 28.93 and 24.82q, DCP 2.52 and 2.33q abd TDN 17.90 and 14.25q/ha from natural and napier grass respectively. Feed DM, DCP and TDN intake were significantly higher on natural grass feeding but digestibility coefficients and nutritive value of the grasses were similar in mithun clves. Feed nutrients obtained from both the natural and cultivated grasses were similarly utilized by the mithun calves and so cultivation of napier grass could be adopted on the hillock of. NEHR to mitigate the blance between availability and nutrients requirement of mithun.